Ultrasound assessment of insular development in adequate-for-gestational-age fetuses and fetuses with early-onset fetal growth restriction using 3D-ICRV technology - Xue, Jinfeng; Xue, Jinluan; Ru, Yanhui; Zhang, Ge; Yin, Hong; Liu, Dequan (Frontiers in Medicine, 2024)
Objective This study aimed to evaluate the growth trajectory of the insula in adequate-for-gestational-age (AGA) and early-onset fetal growth restriction (FGR) fetuses and analyze the difference between the two groups using three-dimensional inversion crytal and realistic vue technique (3D-ICRV). Methods Singleton pregnant women, with a gestational age ranging from 20 to 32+6 weeks, who underwent routine examinations at Shandong Maternal and Child Care Hospital between March 2023 and December 2023 were included. The participants were divided into two groups: the FGR and AGA fetuses. Three-dimensional volumes were obtained using transabdominal ultrasound in the transverse section of the fetal hypothalamus based on different gestational ages. 3D-ICRV rendering technology was used for 3D imaging of the fetal insula. Volumes with a clear display of the insula were selected. We observed the morphology of the insula, and measured the area and circumference of the insula. By evaluating the growth trajectory of the insula in AGA and FGR fetuses, differences in insular development between the two groups were compared. Results Overall, 203 participants were included in this study, with 164 and 39 in the AGA and FGR groups, respectively. The 3D volumes were successfully acquired, and the area and circumference of the insula were measured using 3D-ICRV imaging technology. We found that as gestational age increased, the area and circumference of the insula gradually increased and showed positive correlations with the gestational age, with no significant changes in morphology. The growth rate of insular area and insular circumference in the FGR group is slower than that in the AGA group (insular area: 0.15 vs 0.19 cm2 / week, insular circumference: 0.25 vs 0.28 cm / week). The area and circumference of the insula in the FGR group were significantly different from those in the AGA group (insular area: p = 0.003, insular circumference: p = 0.004). Conclusion The measured values of the insula using 3D-ICRV identify the differences in insular development between the FGR and AGA fetuses. The findings of this study have important implications for the prenatal evaluation of cortical development and maturity in FGR fetuses and further clinical consultation and management.